2008
DOI: 10.1177/1525740108326034
|View full text |Cite
|
Sign up to set email alerts
|

Adult People With Language Impairment and Their Life Situation

Abstract: Psychosocial outcome of language impairment (LI) was explored in interviews with three adults with LI (as children attended specialized boarding school) and four of their parents. The informants with LI expressed acceptance of LI and described themselves as independent. With driving education with adjusted pedagogy and initial governmental support, the informants with LI acquired driving licenses, developed work skills, and were paid salary by employers. Academic success was accredited to the specialized board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…For example, young adults with a history of early LI have significantly higher rates of mental health problems ( Beitchman et al, 2001 ; Conti-Ramsden & Botting, 2008 ; Law, Rush, Schoon, & Parsons, 2009 ; Schoon, Parsons, Rush, & Law, 2010 ). Difficulties in social adjustment and friendship maintenance are often reported in young adults with LI ( Clegg, Hollis, Mawhood, & Rutter, 2005 ; Törnqvist, Thulin, Segnestam, & Horowitz, 2009 ; Whitehouse, Watt, Line, & Bishop, 2009 ). Voci, Beitchman, Brownlie, and Wilson (2006) found that the incidence of social phobia (fear of interacting with others, speaking to small or large groups, and being observed) was more than twice as high in 19-year-olds with LI (who had been identified first at age 5 years) than in peers with typical language skills.…”
Section: Social Confidence In Individuals With LI In Early Adulthoodmentioning
confidence: 99%
“…For example, young adults with a history of early LI have significantly higher rates of mental health problems ( Beitchman et al, 2001 ; Conti-Ramsden & Botting, 2008 ; Law, Rush, Schoon, & Parsons, 2009 ; Schoon, Parsons, Rush, & Law, 2010 ). Difficulties in social adjustment and friendship maintenance are often reported in young adults with LI ( Clegg, Hollis, Mawhood, & Rutter, 2005 ; Törnqvist, Thulin, Segnestam, & Horowitz, 2009 ; Whitehouse, Watt, Line, & Bishop, 2009 ). Voci, Beitchman, Brownlie, and Wilson (2006) found that the incidence of social phobia (fear of interacting with others, speaking to small or large groups, and being observed) was more than twice as high in 19-year-olds with LI (who had been identified first at age 5 years) than in peers with typical language skills.…”
Section: Social Confidence In Individuals With LI In Early Adulthoodmentioning
confidence: 99%
“…Wadman et al (2008) reported that young adults with an SLI may be at risk of lower global self-esteem when compared with their peers. Individuals with an SLI also avoided communicatively demanding situations or times when they were required to speak to someone new, such as a cashier (Törnqvist et al 2009).…”
Section: Communication and Self-esteemmentioning
confidence: 99%
“…Individuals with an SLI also avoided communicatively demanding situations or times when they were required to speak to someone new, such as a cashier (Törnqvist et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…6 Adults report social isolation and anxiety, particularly regarding situations that are communicatively demanding. 7 A major challenge regards how and when best to intervene to reduce morbidity and to improve outcomes; this requires a much better understanding of the natural history of language delay than is currently available. As highlighted in a major 2006 US Preventive Services Task Force systematic review, 8 neither screening nor directly assessing the communication skills of very young children has proved particularly helpful at the population level, because of time requirements, costs, and poor sensitivity and specificity of existing language screens.…”
mentioning
confidence: 99%